Ideas and perspectives: Alleviation of functional limitations by soil organisms is key to climate feedbacks from arctic soils - Blume-Werry, Gesche; Klaminder, Jonatan; Krab, Eveline J.; Monteux, Sylvain (Biogeosciences, 2023)
Arctic soils play an important role in Earth's climate system, as they store large amounts of carbon that, if released, could strongly increase greenhouse gas levels in our atmosphere. Most research to date has focused on how the turnover of organic matter in these soils is regulated by abiotic factors, and few studies have considered the potential role of biotic regulation. However, arctic soils are currently missing important groups of soil organisms, and here, we highlight recent empirical evidence that soil organisms' presence or absence is key to understanding and predicting future climate feedbacks from arctic soils. We propose that the arrival of soil organisms into arctic soils may introduce “novel functions”, resulting in increased rates of, for example, nitrification, methanogenesis, litter fragmentation, or bioturbation, and thereby alleviate functional limitations of the current community. This alleviation can greatly enhance decomposition rates, in parity with effects predicted due to increasing temperatures. We base this argument on a series of emerging experimental evidence suggesting that the dispersal of until-then absent micro-, meso-, and macroorganisms (i.e. from bacteria to earthworms) into new regions and newly thawed soil layers can drastically affect soil functioning. These new observations make us question the current view that neglects organism-driven “alleviation effects” when predicting future feedbacks between arctic ecosystems and our planet's climate. We therefore advocate for an updated framework in which soil biota and the functions by which they influence ecosystem processes become essential when predicting the fate of soil functions in warming arctic ecosystems.